Production of human recombinant neurotrophins for biomedical studies - L. M. Rafieva; D. R. Safina; I. V. Demidyuk; S. V. Kostrov (Тонкие химические технологии, 2011)
The genes of nerve growth factor (NGF), brain neurotrophic factor (BDNF) and human neurotrophic factor 3 (NT-3) were cloned and expressed in Escherichia coli. Methods of purification and renaturation of the proneurotrophins were developed. It was shown that the recombinant pro-NGF, pro-BDNF and pro-NT-3 induce a differentiation of chicken dorsal root ganglia cell culture.